A unilateral medial frontal cortical lesion impairs trial and error learning without visual control. (August 2015) - Amiez, Céline; Champod, Anne Sophie; Wilson, Charles R.E.; Procyk, Emmanuel; Petrides, Michael
Abstract: There is considerable debate regarding the involvement of the medial frontal cortex in motor and cognitive functions. Recent neuroimaging data suggest a fundamental underlying process that links the motor and cognitive roles of the mid-cingulate cortex (MCC), namely the processing of feedback during trial and error learning in the cingulate motor region that is related to the modality of the feedback. These data suggest that the specific motor context of a task may be a critical determinant of how its outcome is processed in the MCC. We assessed a patient before and after surgery for brain tumour removal in the medial frontal cortex, and a group of matched control subjects. Subjects had to find by trial and error the stimulus associated with the correct feedback amongst four or five similar stimuli. Subjects performed the task in two different visuo-motor contexts: with the response pad and hand visible and with no sight of either pad or hand. The patient showed a selective impairment in this task relative to control subjects in the hardest conditions and the impairment was most marked when the response pad and the hand were not visible. The results support a specific role of the medial frontal cortex in the construction of a sensorimotor representation of choices and related feedback by encoding the contingency between an efference copy of the action and its outcome. Highlights: Strong deficits in a learning task are observed in a patient with a MFC lesion. Deficits were especially strong when hand responses were not visually-controlled. The MFC constructs a sensorimotor representation of choices and related feedback.